Studi Kenyamanan untuk Aktivitas di Lanskap Hutan Kota UGM Studi Kasus: Klaster Agro UGM - Siti Nurul Rofiqo Irwan; Kaharuddin Kaharuddin (Jurnal Ilmu Kehutanan, 2010)
A Study of Comfort for Activities in Urban Forest Landscape of UGM; Study Case: Agro Cluster UGMThe phenomenon of global warming has caused discomfort activity in urban area. Greening in open space of Gadjah Mada University campus has been developed as urban forest landscape that supporting good environment produced high comfort for activity and enhancing urban conservation. The research objectives were to observe the comfort for activity in urban forest landscape, to observe the canopy coverage of urban forest and to reveal the effect of tree canopy coverage to the comfort for activity. Data collection was carried out by visual observation, questioner, micro climate measurement, and hemispherical images of the tree canopy coverage. Data were analyzed by descriptive statistics. The tree canopy coverage was calculated by the Sky View Factor (SVF) of hemispherical images. Research results showed that activity types in the urban forest landscape were study (10%), sitting (37%), meeting (39%), others (14%) at spread of sitting areas. Some factors that affect the comfort for activity in urban forest landscape were aesthetic, lower temperature, fresh air, inspirited area, and listened bird voice. The respondents (82%) said that the urban forest landscape was comfort for activity at whole time of 07.00 - 17.00 by the condition of local climate presented by air temperature at 29.7 - 32.6°C, normal humidity at 61.5 -74.1% and breeze wind velocity at 0.6 - 2.8 m/s. Tree canopy of urban forest landscape had covered more than 50% identified by Sky View Factor (SVF 0.026-0.446). The tree canopy coverage of urban forest created tree shaded areas for the activities which showed thermally comfort because of microclimate controlled by urban forest.